Der er ikke langt fra tanke til handling: Om semantiske typer og systematisk polysemi i Den Danske Begrebsordbog - Nimb, Sanni (Danske Studier, 2016)
A fundamental aspect of word sense description in formal lexical semantics is the so-called ‘semantic type’, e.g. [Person], [Act] and [Time]. While such types play a major role in the compilation of formal lexicons, i.e. WordNets, they are not traditionally considered when dictionaries and thesauri aimed at human users are written. This paper concerns the intentional use of semantic types as the internal ordering principle of the thematically defined sections in a newly published Danish thesaurus, Den Danske Begrebsordbog. The set of semantic types is defined and discussed. Some types are considered more closely related than others and thereby aspire to be merged in cases where a given section contains only a few words. Different examples of such flexible groups across types are presented and the employment of these is justified. The vocabulary of the thesaurus originates from a comprehensive, monolingual Danish dictionary, and the paper discusses the differences between semasiological and onomasiological sense distinctions as regards the use of semantic types as a criterion and, on a similar note, the treatment of regular polysemy. The thesaurus provides a rich source with regards to the study of regular polysemy in Danish, and a specific case is presented, namely the regular pattern between ‘acts’ on the one hand and ‘ideas’ on the other hand.